The Influence of a Continuum Background on Carrier Relaxation in InAs/InGaAs Quantum Dot - Visimberga Giuseppe; Rainò Gabriele; Salhi Abdelmajid; Todaro Maria; De Vittorio Massimo; Passaseo Adriana; Cingolani Roberto; De Giorgi Milena (Nanoscale Research Letters, 2007)
Abstract We have investigated the ultra-fast carrier dynamics in Molecular Beam Epitaxy (MBE)-grown InAs/InGaAs/GaAs quantum dots (QDs) emitting at 1.3 μm by time resolved photoluminescence (TRPL) upconversion measurements with a time resolution of about 200 fs. Changing the detection energies in the spectral region from the energy of the quantum dots excitonic transition up to the barrier layer absorption edge, we have found that, under high excitation intensity, the intrinsic electronic states are populated mainly by carriers directly captured from the barrier.